WILLINGNESS TO BODY DONATION AMONG THE POPULATION OF CORDOBA IN ARGENTINA - Susana N. Biasutto; Lucía M. Navarro; Sofía G. Siemsen; Florencia Turri; Nicolás Longoni; Atilio J. Bertocchi Valle; Oscar P. David; Marcos A. Spinelli; Daniel Urrutia; Diego M. Weigandt; Federico N. De Oro; Isaias E. Molina Vargas (Asociación Argentina de Anatomía Clínica, 2021)
Corpses are an irreplaceable resource for teaching and research in Anatomy. Voluntary donation is the source of cadavers, but in the  National University of Cordoba we are struggling with a critical shortage due to the lack of an organized donation program. The objective of this study was to know the attitude of general population of the city of Cordoba about this subject and the profile of potential donors to develop a program. A survey was randomly distributed among older than 18 years. The questionnaire included demographic, educational, laboral and religious aspects and specific ones related to the willingness to donate the own body and reasons to do it, knowledge about this possibility, interest in further information. Two thousand and thirty responses were obtained from a population so diverse that we considered it as representative of the city. Among the respondents, 80% should be willing to donate organs for transplantation and 41% the whole body; with 45% who said to know about donation and 54% interested in more information. Main motives to donate were related to support teaching, research and science; while the main reason not to donate was associated with insuficient information. The profile of potential donors was obtained from the analysis of all the variables and we compared with other studies demonstrating that not only cultural and religious aspects may determine the willingness to donate but also the level of public information and facilities to register as donors.